Whistleblowing Disclosure of the Banking Sector - Lilik Handajani; Saipul Arni Muhsyaf; Ayudia Sokarina (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
The purpose of this study is to describe the disclosure of the whistleblowing system (WBS) in public banks listed on the Indonesia Stock Exchange. Content analysis is carried out on information related to the disclosure of the whistleblowing system in the 2018-2020 bank annual report. The banking sector has deployed a rising number of whistleblowing systems (WBS) over the past three years, from 2018 to 2020, according to the study's findings. Disclosure of the WBS Whistle in the banking sector can be classified into domains: bank commitments to the implementation of WBS, the mechanism for reporting violations and types of violations reported, protecting the whistleblower's confidentiality, and investigating and evaluating the effectiveness of the WBS. The results of this study imply that the Bank's whistleblowing system policy is a governance mechanism as an early warning signal to detect indications of violations, alleged ethical irregularities and fraud.